The complete ElfQuest. Volume three - Pini, Wendy; Pini, Richard; Byam, Sarah E. (Dark Horse Books, a division of Dark Horse Comics, Inc., 2016)
"In this volume you will enjoy the classic standalone stories of 'ElfQuest's Hidden Years,' such as Strongbow's courageous battle to save the life of his wolf-friend Lashpaw, the raising of an abandoned human cub by the compassionate Tyleet, and Skywise's dark origin story that reveals why he holds such hard feelings against humans. Also collected is the entire Dreamtime series, in which the Wolfriders share the secret dreams from their centuries-long sleep and wonder what these visions may mean for their future!"--Back cover.